Field Evaluation of Culture plus Latex Sweep Serotyping for Detection of Multiple Pneumococcal Serotype Colonisation in Infants and Young Children - Paul Turner (2018)
Background:Nasopharyngeal swab (NPS) culture by World Health Organisation (WHO) methodology underestimates multiple pneumococcal serotype colonisation compared to a simple culture and latex sweep method. The impacts of this on descriptions of pneumococcal serotype distributions and colonisation dynamics in infancy are not clear.Methods:8,736 NPS collected from infants enrolled into a longitudinal study were processed to evaluate the field utility of the latex sweep method. 1,107 had previously been cultured by WHO methodology. Additionally, colonisation results were compared in 100 matched pairs of infants, where swabs from an individual were cultured either by WHO or latex sweep method.Results:In 1,107 swabs cultured by both methods, the latex sweep method was three times more likely to detect colonisation with multiple pneumococcal serotypes than the WHO method (p<0.001). At least one common serotype was identified in 91.2% of swabs from which typeable pneumococci were detected by both methods. Agreement improved with increasing colonisation density (p = 0.03). Estimates of age at first pneumococcal acquisition and colonisation duration were not affected by culture/serotyping method. However, a greater number of serotype carriage episodes were detected in infants cultured by latex sweep (p = 0.03). The overall rate of non-vaccine type pneumococcal acquisition was also greater in infants cultured by latex sweep (p = 0.04).Conclusions:Latex sweep serotyping was feasible to perform on a large specimen collection. Multiple serotype colonisation detection was significantly improved compared with WHO methodology. However, use of the latex sweep method is unlikely to significantly alter colonisation study serotype distribution or colonisation dynamics results. © 2013 Turner et al.